Demographics and health profile on precursors of non-communicable diseases in adults testing for HIV in Soweto, South Africa: a cross-sectional study. Issue 12 (15th December 2019) - Hopkins, Kathryn L; Hlongwane, Khuthadzo; Otwombe, Kennedy; Dietrich, Janan; Cheyip, Mireille; Khanyile, Nompumelelo; Doherty, Tanya; Gray, Glenda E
Abstract : Objectives: This cross-sectional study investigated the burden of HIV-non-communicable disease (NCD) precursor comorbidity by age and sex. Policies stress integrated HIV-NCD screenings; however, NCD screening is poorly implemented in South African HIV testing services (HTS). Setting: Walk-in HTS Centre in Soweto, South Africa. Participants: 325 voluntary adults, aged 18+ years, who provided written or verbal informed consent (with impartial witness) for screening procedures were enrolled. Primary and secondary outcomes: Data on sociodemographics, tuberculosis and sexually transmitted infection symptoms, blood pressure (BP) (≥140/90=elevated) and body mass index (<18.5 underweight; 18.5–25.0 normal; >25 overweight/obese) were stratified by age-group, sex and HIV status. Results: Of the 325 participants, the largest proportions were female (51.1%; n=166/325), single (71.5%; n=231/323) and 25–34 years (33.8%; n=110/325). Overall, 20.9% (n=68/325) were HIV infected, 27.5% (n=89/324) had high BP and 33.5% (n=109/325) were overweight/obese. Among HIV-infected participants, 20.6% (14/68) had high BP and 30.9% (21/68) were overweight/obese, as compared with 29.3% (75/256) and 12.1% (31/256) of the HIV-uninfected participants, respectively. Females were more likely HIV-infected compared with males (26.5% (44/166) vs 15.1% (24/159); p=0.012). In both HIV-infected and uninfected groups, high BP was most prevalent in those aged 35–44 years (25% (6/24) vs 36% (25/70); p=0.3353) and >44 years (29% (4/14) vs 48% (26/54); p=0.1886). Males had higher BP than females (32.9% (52/158) vs 22.3% (37/166); p=0.0323); more females were overweight/obese relative to males (45.8% (76/166) vs 20.8% (33/159); p<0.0001). Females were more likely to be HIV infected and overweight/obese. Conclusion: Among HTS clients, NCD precursors rates and co-morbidities were high. Elevated BP occurred more in older participants. Targeted integrated interventions for HIV-infected females and HIV-infected people aged 18–24 and 35–44 years could improve HIV public health outcomes. Additional studies on whether integrated HTS will improve the uptake of NCD treatment and improve health outcomes are required.